2012
DOI: 10.1021/bi301195f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Membrane Pore Formation by Bax Protein Carboxyl Terminus

Abstract: Bax protein plays a key role in mitochondrial membrane permeabilization and cytochrome c release upon apoptosis. Our recent data have indicated that the 20-residue C-terminal peptide of Bax (BaxC-KK; VTIFVAGVL-TASLTIWKKMG), when expressed intracellularly, translocates to the mitochondria and exerts lethal effect on cancer cells. Moreover, the BaxC-KK peptide, as well as two mutants where the two lysines are replaced with glutamate (BaxC-EE) or leucine (BaxC-LL), have been shown to form relatively large pores i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
(187 reference statements)
2
14
0
Order By: Relevance
“…In addition, we examined whether the α9 helix (or the α9:α9 interface) might be necessary for the step of pore formation, as α9 appears to be the only region that traverses the MOM before and after pore formation, [21][22][23] and α9 peptides have been proposed to be membranolytic with antitumor activity. 43,58 Thus, understanding α9 membrane topology may reveal novel insight for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we examined whether the α9 helix (or the α9:α9 interface) might be necessary for the step of pore formation, as α9 appears to be the only region that traverses the MOM before and after pore formation, [21][22][23] and α9 peptides have been proposed to be membranolytic with antitumor activity. 43,58 Thus, understanding α9 membrane topology may reveal novel insight for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Single amphipathic helices such as melittin can form relatively stable 'lipidic' pores, 64 and hydrophobic peptides based on Bak or Bax α9 can also permeabilize mitochondria (Supplementary Figures S5a and b) 65 and vesicles. 41,43,46,47 However, green fluorescent protein (GFP) fused to Bax or Bak α9 was not reported to kill cells, 28,32,34,66 and we know of no instance in which a C-terminal transmembrane anchor in a full-length protein takes part directly in forming the pore. We note also that a Bak C terminus is not essential for the step of pore formation, as recombinant Bak with a hexahistidine tag in lieu of its C terminus can bind and permeabilize nickelincorporated liposomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One strategy is to derive peptides from previously characterized, endogenous cellular proteins. This approach takes advantage of the information available on the localization and function of the protein from which the peptide is derived and could inform of the potential [4][5][6]11] molecular target and action of the peptide. Recently, we reported that a 20 amino acid -helical peptide developed from the 9 transmembrane domain of the pro-apoptotic protein, Bax, has cytotoxic actions for cancer cells [4] .…”
mentioning
confidence: 99%